Empowerment of Mojogedang Layer Farm Partners in Utilizing Aloe Vera as a Coating to Extend the Shelf Life of Broiler Eggs - Wijayanti, Desna Ayu; Astuti, Puji; Nugroho, Dimas Fajar; Pratiwi, Oktavia Dewi; Luay, Abyan; Arianto, Pradipta (Pascasarjana Universitas Mataram, 2025)
Aloe vera gel can be used as an edible coating for chicken eggs, providing a natural alternative to chemical preservatives. This activity aimed to empower community members to utilize aloe vera gel as a coating for poultry products, specifically eggs. An interactive discussion involving 20 community members from RW 18, Gebyog Village, Mojogedang District, Karanganyar Regency was conducted. This was followed by an extension program and mentoring on the preparation of aloe vera gel for egg preservation. Results showed an increase in knowledge about food additives, the benefits of aloe vera gel as a coating, and the skills required to prepare aloe vera gel as a coating for chicken eggs. In conclusion, the community's knowledge and skills in utilizing aloe vera gel as a natural coating for chicken eggs have significantly improved